2017
DOI: 10.1088/1361-6633/80/3/036502
|View full text |Cite
|
Sign up to set email alerts
|

Phonons and thermal transport in graphene and graphene-based materials

Abstract: A discovery of the unusual thermal properties of graphene stimulated experimental, theoretical and computational research directed at understanding phonon transport and thermal conduction in two-dimensional material systems. We provide a critical review of recent results in the graphene thermal field focusing on phonon dispersion, specific heat, thermal conductivity, and comparison of different models and computational approaches. The correlation between the phonon spectrum in graphene-based materials and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
215
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(222 citation statements)
references
References 167 publications
(543 reference statements)
6
215
0
1
Order By: Relevance
“…[68,[70][71][72][73][74][75][76] The first studies showed that adding even a small loading fraction of the optimized mixture of graphene and FLG (up to f = 10 vol%) to the pristine epoxy increases its thermal conductivity by a factor of ×25. [86] Prior studies suggested that the graphene-based composite exhibits the "electrical percolation threshold" at rather low loading fractions of graphene or FLG fillers. [77,78] One of the conclusions from the reports of the thermal properties of composites with graphene and FLG is that there exists an optimum range of the filler lateral dimensions, thicknesses, and aspect ratios for heat conduction.…”
Section: Introductionmentioning
confidence: 99%
“…[68,[70][71][72][73][74][75][76] The first studies showed that adding even a small loading fraction of the optimized mixture of graphene and FLG (up to f = 10 vol%) to the pristine epoxy increases its thermal conductivity by a factor of ×25. [86] Prior studies suggested that the graphene-based composite exhibits the "electrical percolation threshold" at rather low loading fractions of graphene or FLG fillers. [77,78] One of the conclusions from the reports of the thermal properties of composites with graphene and FLG is that there exists an optimum range of the filler lateral dimensions, thicknesses, and aspect ratios for heat conduction.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in the thermal conductivity of the resulting composite can come owing to two possible mechanisms. The first one is related to very high intrinsic thermal conductivity of graphene [46] and its good coupling to the matrix materials [41,43,45]. The heat propagates partially via graphene fillers and partially via the matrix material.…”
Section: Testing Of the Photovoltaic Solar Cellsmentioning
confidence: 99%
“…This material has proven to have an unusually high thermal conductivity with intrinsic values in the range of 2000 to 5000 W/mK near room temperature [46]. This is an order of magnitude larger than pure silver [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…It is also worth noting that this technique is the only option without extensive nanofabrication for two‐dimensional materials. In the previous studies, for measuring the thermal conductivity of two‐dimensional materials with Raman thermal technique, the sample was usually suspended over a trench and heated by increasing laser power . According to the heat conduction through the sample surface, the thermal conductivity values could be extracted on the basis of Fourierapos;s equation as: K=χGL2S()italicdPitalicdω, where K is the thermal conductivity, χ G is the temperature coefficient, L is the distance from the middle of the suspended sample to the heat sink, S is the cross‐sectional area, and dω is a peak shift due to the variation dP in the heating power on the sample surface.…”
Section: Iintroductionmentioning
confidence: 99%
“…In the previous studies, for measuring the thermal conductivity of two-dimensional materials with Raman thermal technique, the sample was usually suspended over a trench and heated by increasing laser power. [4][5][6][7][8][9][10] According to the heat conduction through the sample surface, the thermal conductivity values could be extracted on the basis of Fourier's equation as [10] :…”
Section: Iintroductionmentioning
confidence: 99%